2019
DOI: 10.1177/1538192719892148
|View full text |Cite
|
Sign up to set email alerts
|

Latino STEM Scholars, Barriers, and Mental Health: A Review of the Literature

Abstract: Research exploring the participation and retention of Latino/as in STEM (science, technology, engineering, and math) is still in its early stages, but it is shedding light on the lack of representation, why they occur, and what are the outcomes for those that remain in STEM. This review of the literature explores the barriers, stressors, and health issues that emerge for Latino/a STEM faculty. The review includes work on the comprehensive stress, discrimination, and other burdens that contribute to Latino/a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In a study by Alonso (2015), Latinx engineers found their identity was nurtured through participation in the Society of Hispanic Professional Engineers (SHPE) when they created their own engineering familia and obtained disciplinary role models. Nevertheless, Latinx students report their STEM identity and career pursuits often are hampered by a lack of access to socialization opportunities in STEM and all too often experience marginalization, microaggressions, and blatant bias in the academy (López et al, 2019; Malone & Barabino, 2009; Muñoz & Villanueva, 2019; Rodriguez, Cunningham, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Alonso (2015), Latinx engineers found their identity was nurtured through participation in the Society of Hispanic Professional Engineers (SHPE) when they created their own engineering familia and obtained disciplinary role models. Nevertheless, Latinx students report their STEM identity and career pursuits often are hampered by a lack of access to socialization opportunities in STEM and all too often experience marginalization, microaggressions, and blatant bias in the academy (López et al, 2019; Malone & Barabino, 2009; Muñoz & Villanueva, 2019; Rodriguez, Cunningham, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on learning environments, such as postdoctoral appointments, can expand consideration of the way in which context intersects with STEM identity and STEM career pathways. This approach can be particularly useful for underrepresented populations that commonly experience structural barriers in STEM (López et al, 2019; Malone & Barabino, 2009; Muñoz & Villanueva, 2019; Rodriguez, Cunningham, et al, 2019; Talaflan et al, 2019; Yadav et al, 2020). As noted by Kim and Sinatra (2018), drawing attention to the STEM environment can provide new understandings of the contextual messages individuals receive relative to their STEM identity, as well as fresh insights for interested stakeholders who can improve STEM spaces.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The causes of low Latinx representation at all academic levels in STEM are multivariate. Unequal access to education and health care, immigration barriers, family expectations, discrimination, feelings of isolation and perceptions of Latinx students as 'low performing' all contribute to poor recruitment and retention of Latinx trainees and faculty members 4 . Additionally, Latinx researchers at all career levels often do not have appropriate role models to 'see' themselves in influential positions in STEM owing to the low likelihood that their peers and senior mentors are also Latinx.…”
Section: Underrepresentation In Stemmentioning
confidence: 99%
“…This study reveals both the depth of challenges and possibilities facing the science education community. It is important to note that Latinx students are disproportionately under‐represented in STEM in general, and the physical sciences in particular (Muñoz & Villanueva, 2019; National Science Board, National Science Foundation, 2021). The two case study students' perceptions of themselves in relation to physics are consistent with the larger patterns reported by prior studies that examined minoritized students' struggles in pursuing STEM‐related careers (see Estrada et al, 2018 for example).…”
Section: Discussionmentioning
confidence: 99%